2014
DOI: 10.1158/1541-7786.mcr-14-0088-t
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Proteomic and Transcript Analyses Reveal that Stathmin-1 Silencing Inhibits Colorectal Cancer Metastasis and Sensitizes to 5-Fluorouracil Treatment

Abstract: Colorectal cancer metastasis is a major cause of mortality worldwide, which may only be controlled with novel methods limiting tumor dissemination and chemoresistance. High stathmin-1 (STMN1) expression was previously established as a hallmark of colorectal cancer progression and predictor of poor survival; however, the mechanism of action is less clear. This work demonstrates that STMN1 silencing arrests tumor-disseminative cascades by inhibiting multiple metastatic drivers, and repressing oncogenic and mesen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
6
24
0
Order By: Relevance
“…The inhibition of STMN1 reduced cell proliferation over the first 24 hours but not by 48 hours, and reducing STMN1 had no effect on MPM cell clonogenicity. However, inhibiting STMN1 reduced MPM cell motility, supporting earlier studies in gastric (17) and colon cancers (48).…”
Section: Discussionsupporting
confidence: 87%
“…The inhibition of STMN1 reduced cell proliferation over the first 24 hours but not by 48 hours, and reducing STMN1 had no effect on MPM cell clonogenicity. However, inhibiting STMN1 reduced MPM cell motility, supporting earlier studies in gastric (17) and colon cancers (48).…”
Section: Discussionsupporting
confidence: 87%
“…17 Inhibition of STMN1 with small interfering RNA (siRNA) was shown to sensitize cancer cells to 5-FU treatment. 18 However the synergistic effects between 5-FU were question in studies of antistathmin ribozyme with 5-FU or adriamycin, in which both were shown to be additive. 19 Additionally, knockdown of STMN1 blocked tumor growth in vivo in a model of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance to docetaxel with stathmin overexpression may be caused by the microtubule‐destabilizing activity of stathmin, which may diminish binding to docetaxel and increase binding to vincristine‐like drugs . Chemoresistance to cisplatin and 5‐fluorouracil with stathmin overexpression may be caused by the participation of stathmin overexpression in the cellular response to DNA damage and caspase‐6‐mediated cellular apoptosis, as described in previous studies conducted in head and neck cancer or colorectal cancer, respectively . To some extent, these reasons lead to the unsatisfactory clinical benefit of TPF induction chemotherapy in OSCC patients with high stathmin expression.…”
Section: Discussionmentioning
confidence: 93%